Developing web for learning object oriented programming (OOP) using videos / Farah Syazwani Roslan - Roslan, Farah Syazwani Roslan (2020)
The purpose of this project is to inform students on learning certain topics using visual styles of learning to provide a creative person to have a better performance and a good sense of understanding by learning Object Oriented Programming knowledge. Learning using video is a good helper on giving a better understanding for students to learn some topics or techniques based on the videos shown. This study can show that this style of learning using video as the visual learning style could contribute to the effectiveness of learning and provide the satisfaction of students to have more understanding on learning certain topics that acts as a supportive and a good helpers for students. In technology, learning using videos helps to demonstrate students to gives short instructions in a short time and provide a better understanding and great explanation during learning Object Oriented Programming knowledge. Practical demonstration on using video as style of learning may provide easiness during delivering or retrieving some information. Nowadays, most of students even the instructors are more preferred in having the easiest and the fastest way of catching knowledge in such a short time also adapting new knowledge provide confidence and motivate them to learn effectively.